Overcoming women's isolation at work: The effect of organizational structure and practices on female managers' workplace relationships. (May 2022) - Shin, Hwajin; Kim, Soohan
Successful career outcomes depend on maintaining positive relationships with and evaluations from supervisors and peers. Recognizing that structure frames behaviors and perceptions, this study explores the impact of organizational structure and practices on the relationships of 598 women in 298 Korean companies using longitudinal data from 2010 to 2016. The results from fixed-effects models show that corporate structure and practices shape female managers' relationships with supervisors and peers. Gender equality practices improve relationships with both men and women. By contrast, diversity programs have negative effects on female managers' relationships with female supervisors and peers, and work–life programs show mixed results. However, in firms with female executives and firms that encourage men to use parental leave, diversity programs and work–life practices stimulate positive relationships with both male and female supervisors and peers. This study suggests that organizational contexts, rather than intrinsic gender preferences, shape women's relationships in the workplace.